Melatonin ameliorates methionine- and choline-deficient diet-induced nonalcoholic steatohepatitis in rats - (:unkn) unknown (WILEY, 2009)
Nonalcoholic steatohepatitis (NASH) may progress to advanced fibrosis and cirrhosis. Mainly, oxidative stress and excessive hepatocyte apoptosis are implicated in the pathogenesis of progressive NASH. Melatonin is not only a powerful antioxidant but also an anti-inflammatory and anti-apoptotic agent. We aimed to evaluate the effects of melatonin on methionine- and choline-deficient diet (MCDD)-induced NASH in rats. Thirty-two male Wistar rats were divided into four groups. Two groups were fed with MCDD while the other two groups were fed a control diet, pair-fed. One of the MCDD groups and one of the control diet groups were administered melatonin 50 mg/kg/day intraperitoneally, and the controls were given a vehicle. After 1 month the liver tissue oxidative stress markers, proinflammatory cytokines and hepatocyte apoptosis were studied by commercially available kits. For grading and staging histological lesions, Brunt et al.'s system was used. Melatonin decreased oxidative stress, proinflammatory cytokines and hepatocyte apoptosis. The drug ameliorated the grade of NASH. The present study suggests that melatonin functions as a potent antioxidant, anti-inflammatory and antiapoptotic agent in NASH and may be a therapeutic option.
Keywords: apoptosis; choline; cytokine; glutathione; interleukin; malondialdehyde; melatonin; methionine; steatohepatitis; superoxide dismutase; tumor necrosis factor alpha; MITOCHONDRIAL PERMEABILITY TRANSITION; NUTRITIONAL MODEL; LIVER; APOPTOSIS; ROSIGLITAZONE; EXPRESSION; PATHWAYS; NECROSIS; CYP2E1